School Information System Innovation by Eduversal through Edunav Implementation in Indonesia: A Case Study at SMP-SMA Kesatuan Bangsa Bilingual Boarding School Yogyakarta - Sidik, Dede Syahril; Pitoyo, Agus Joko; Ikhwan, Hakimul (Populasi, 2023)
Technological innovation is a science which will continue to develop over time, therefore knowledge, skills, and understanding are needed in life, especially in educational institutions. Many researchers have conducted studies on educational system innovations because the implementation of information systems in educational institutions has made a positive contribution to education management. The existence of an educational information system provides convenience in communicating, exchanging information quickly and accurately, as well as an increase in educational services. This research is based on the implementation of the Edunav Information System as an information system innovation which is applied to educational institutions. Edunav is an application for student progress reports in learning in the form of e-reports. The form of the reported activity from the learning process includes attendance, homework, quizzes, unit tests and so on. This study aims to uncover the factors which drive the Edunav Information System to be implemented and the benefits derived from it at the SMP-SMA Kesatuan Bangsa Bilingual Boarding School Yogyakarta. The method used in this research is a qualitative research method with a case study approach. The data of this research are obtained from in-depth interviews, observation, and literature study. In-depth interviews were conducted with several informants by means of a snowball. The results of this study show that there are several factors which encourage the implementation of the Edunav Information System at the Kesatuan Bangsa School, which are 1) complex problems occur in the field as there is no integrated system; 2) manual data processing which is recorded in books; 3) the existence of school initiatives to make changes from conventional to digital schools by increasing the use of information technology; 4) increasing competitiveness among schools is significant, especially for private schools. The perceived benefits of the Edunav Information System are 1) as an information system for schools, parents, and students; 2) as a media to support education; 3) as a means of control for schools, parents and students.